A technical and economical evaluation of RP technology for RTM tooling - Dippenaar, D. J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.